UM ESTUDO EMPÍRICO SOBRE AS PERSPECTIVAS DE AMPLIAÇÃO DAS RELAÇÕES COMERCIAIS ENTRE BRASIL E CHINA - Mendes, Adriana Toledo; Azevedo, André Filipe Zago de; Terra, Paulo Renato Soares (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This paper identifies those Brazilian products, at six-digit level of NCM, with greater perspectives of increasing their exports to China, through the evaluation of the Brazilian export competitiveness and the Chinese import dynamism. The analysis of Brazilian competitiveness is based on the Index of Revealed Comparative Advantage (RCA), while the Chinese import dynamism is obtained by looking at those products which showed the greater increase in imports in the period 2000-2007, which coincides with China accession to WTO. Both indicators consider the HS classification at 06 digit level, in the years 2000, 2004, 2005, 2006 e 2007. Besides, it was identified the technological intensity degree of those Brazilian products with major potential of exports growth to China. From an universe of more than 5 thousand products, only 92 satisfied both criteria, being both competitive in Brazil and dynamic in the Chinese market, with great possibilities to increase the bilateral trade. It was possible to note that the Brazilian exports to China are highly concentrated in few products, especially ores, soy, cellulose and vegetable oils, where it shows comparative advantage and China a strong import growth, which Chinese imports seems to be intense in those products in which Brazil shows competitiveness.